Comparative evaluation of graph construction methods for individual brain metabolic network from FDG-PET images: an ADNI study in healthy subjects. - Tuan, Pham Minh; Horowitz, Tatiana; Adel, Mouloud; Wojak, Julien; Trung, Nguyen Linh; Guedj, Eric (European Journal of Nuclear Medicine & Molecular Imaging, 2026)
Purpose: Connectivity analyses of fluorodeoxyglucose positron emission tomography (FDG-PET) static images provide a valuable means of investigating brain network organization by capturing metabolic activity at rest. Graph theory is emergently applied to model these networks at individual level; however, the choice of graph construction method can significantly impact analytical outcomes. Methods: In this study, we systematically evaluate and compare methods for building individual graphs from FDG-PET images in healthy control subjects. Specifically, we assess five methods, categorized into mean-based graphs and probability density function (PDF)-based graphs, using two criteria: structural similarity between individual and group-level graphs, and their hub topology structure analysis. Results: Our findings indicate that the Effect Size-based (ES) method best preserves group-level graph structure, achieving 98.9% similarity for the averaged graph while also maintaining around 84% similarity for individual graphs. Among PDF-based approaches, the Wasserstein (WA) method, with its adaptability in PDF-based settings, provides the highest similarity across both averaged (82.5%) and individual (79.1%) graphs, with its adaptive in PDF-settings, making it the most effective for multi-scale network analysis. Meanwhile, Dynamic Time Warping (DTW) captures the highest individual variability, as reflected by its largest variation among individual graphs (11.5%). Conclusion: This analysis highlights the unique strengths and limitations of each method, emphasizing the critical importance of careful method selection tailored to specific research objectives. Additionally, our study suggests a framework for selecting the appropriate methods, with implications for further both research and clinical applications.